Human papillomavirus (HPV): systemic treatment with Gene-Eden-VIR/Novirin safely and effectively clears virus - Polansky H; Itzkovitz E; Javaherian A (Dove Medical Press, 2017)
Hanan Polansky, Edan Itzkovitz, Adrian Javaherian The Center for the Biology of Chronic Disease, Valley Cottage, NY, USA Purpose: This paper reports the results of a clinical study that tested the effect of systemic treatment with the botanical product Gene-Eden-VIR/Novirin on the clearance rate (also called time to clearance) of the human papillomavirus (HPV). The study compared the clearance rate in treated and untreated individuals suffering from a symptomatic HPV infection. The data on the untreated individuals were obtained by reverse engineering of the Kaplan–Meier figures in five published papers. Materials and methods: The study included 59 treated participants. All participants were suffering from a symptomatic HPV infection prior to the commencement of treatment. The treatment was one to four capsules of Gene-Eden-VIR/Novirin per day. The duration of treatment was 2–12 months. The study included five groups of external controls with diverse characteristics. Results: The mean time to clearance in Gene-Eden-VIR/Novirin-treated individuals was 5.1 months or 151.5 days (95% CI: 4.2–5.9 months or 95% CI: 125.7–177.3 days, respectively). The median time to clearance was 3.5 months. The mean time to clearance in the five untreated groups ranged from 6.9 to 20.0 months (P<0.0001 for the difference between treatment group and each untreated group). Also, 100% of the participants in the treatment group were HPV free at the end of 12 months vs 53%, 52%, 65%, 20%, and 77% in the untreated control groups. The treated participants reported no adverse experiences. Conclusion: This clinical study has two major contributions. First, it showed that systemic treatment with the natural Gene-Eden-VIR/Novirin decreased the time to HPV clearance, increased the percentage of HPV-free individuals, and caused no adverse experiences in individuals suffering from a symptomatic HPV infection. Since there are no other systemic treatments for symptomatic HPV infections, this study presents highly valuable information on the clinical effects of the first treatment in this category. Second, the study presents a new method for conducting clinical studies that addresses one of the major deficiencies associated with the practice of the randomized controlled trial method.Keywords: natural treatment, HPV, efficacy, safety, Gene-Eden-VIR/Novirin